Someone's got a screw loose - Krulik, Nancy E.; Burwasser, Amanda Elizabeth (Krulik, Nancy E. Project droid, 2018)
An invitation to a birthday party becomes a recipe for disaster when Java's secret is nearly exposed by a nosy reporter.